Surgical treatment of rare peripheral nerve lesions: long-term outcomes and quality of life - Savić, Andrija; Lepić, Milan; Grujić, Jovan; Mićić, Aleksa; Stojiljković, Aleksandra; Putra, Gunna Hutomo; Terzić, Andrej; Vujić, Lazar; Rasulić, Lukas (Frontiers in Oncology, 2025)
IntroductionRare peripheral nerve lesions comprise a histologically diverse group of neoplastic and non-neoplastic entities, characterized by infrequent occurrence and variable clinical presentations, presenting significant diagnostic and therapeutic challenges. This study presents eight cases of surgically treated rare peripheral nerve lesions with previously unreported long-term outcomes involving quality of life (QOL) assessment.MethodsA retrospective analysis was conducted on medical records from 2012 to 2022 to identify surgically treated cases of rare peripheral nerve lesions, selecting eight cases based on determined inclusion and exclusion criteria. Long-term outcomes and QOL were assessed 12 months post-surgery by patient examination, control imaging and self-reporting questionnaires.ResultsThe study included 4 benign (hemangioblastoma, angiomatoid fibrous histiocytoma, endometriosis (n=2)) and 4 malignant lesions (NTRK-rearranged spindle cell neoplasm, lymphoma, metastatic breast carcinoma (n=2)). Even though benign lesions generally presented with better outcomes, this was more closely related with level of nerve invasion and postoperative sequele, rather than presence of malignancy.DiscussionBecause of a global lack of experience in handling such cases, this study aimed to present the cases we encountered in detail to serve as a basis for future literature reviews. The findings highlight the importance of individualized treatment strategies and long-term follow-up to optimize functional recovery and patient well-being.